Study of hematite recovery by reverse flotation of mixed minerals inHuancavelica - Rodriguez Deza, Jorge Wáshington (2025)
In the present investigation, the reverse flotation method was used to recover hematite in Huancavelica, supported by optical microscopy of arepresentative sample of the mineral, which identified hematite with a distribution of 29.07%, pyrite was observed occupying a volume of 50%,electrum, goethite and gangues in a lesser distribution.Chemical tests determined a head grade of 22.07% hematite and 20.11% total sulfur. The grinding tests of the mineral determined that the P80responded to the model: P80 = 7.7642t² - 230.23t + 1629.3 with a correlation of 94.13%, which was considered to evaluate the recovery of hematitebased on the granulometry of the process.The particle size evaluation tests determined that the recovery decreases when the grinding time increases, and that the appropriate granulometrywas 250 μm. Having determined the particle size variable, the dosage of starch as an oxide depressant was evaluated, whose best reverse flotationtest achieved a recovery of 97.09% of hematite with a concentrate quality of 55.14% and a ratio of 1.62, using 150 g/TM of corn starch (5%), 60 g/TM of xanthate Z-11 (1%), 30 g/TM of pine oil.